Overexpression of MEKK18 from Arabidopsis pumila in rice significantly enhances stress resistance at the early stage - Junrong Li; Yilin Yang; Zhanglun Sun; Edwin Afriyie Owusu; Leiming Liu; Tianrun Mei; Qingli Zhang; Xianzhong Huang (PLoS ONE, 2025)
The mitogen-activated protein kinase (MAPK) signaling cascade is a crucial signaling component of eukaryotic cells. It senses endogenous or exogenous stimuli and exerts a critical regulatory influence on stress responses. The MAP kinase kinase kinase (MEKK) gene is located upstream in the MAPK cascade. It is extensively engaged in plant growth and development, playing a pivotal role in tolerance to abiotic stresses such as salt, drought, and extreme temperatures. Arabidopsis pumila, a short-lived cruciferous plant native to the southern desert area of the Gurbantünggüt Desert in Xinjiang exhibits excellent stress adaptation and contains a rich array of stress resistance genes. Previous research has demonstrated that the expression of ApMEKK18 is continuously upregulated under saline stress, although its function in the response to this type of abiotic stress is unclear. The findings of this study reveal that the ApMEKK18 protein is localized in the cell nucleus, and the ApMEKK18 gene is upregulated in response to abscisic acid (ABA), NaCl, PEG6000, and mannitol, exhibiting varying expression patterns under different conditions. Using Agrobacterium-mediated transformation, we overexpressed ApMEKK18 in rice. Compared to the control variety Nipponbare (NP), no substantial differences were observed in plant height, number of primary and secondary branches, grain width, and thickness in the ApMEKK18-overexpressing transgenic rice. However, the number of tillers, panicle length, grain length, 1,000-grain weight, and single-plant yield were significantly increased. Furthermore, ApMEKK18 overexpression enhanced seed germination under high salt and ABA stress conditions, while reducing sensitivity to exogenous ABA and improving salt tolerance in seedlings. The results of this study provide a theoretical foundation for further research on the function of ApMEKK18 and lay the groundwork for mining stress-resistance genes from A. pumila. Additionally, the findings offer insights into improving crop stress tolerance through genetic engineering.